A multi-satellite framework to rapidly evaluate extreme biosphere cascades The Western US 2021 drought and heatwave - Feldman, Andrew F (Global change biology, 2023)
© 2023 Jet Propulsion Laboratory, California Institute of Technology and The Authors. Government sponsorship acknowledged. Global Change Biology published by John Wiley & Sons Ltd. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA.